Bridged cyclophosphazenes resulting from deprotonation reactions of cyclotriphophazenes bearing a P-NH group - Besli, Serap; Coles, Simon J.; Davies, David B.; Kilic, Adem; Shaw, Robert A. (Royal Soc Chemistry, 2011)
Cyclotriphosphazene derivatives containing a P-NHR group in the side-chain react in the presence of a strong base to form stable intermolecular bridged products. Reaction of sodium hydride with mono-spiro cyclophosphazene derivatives having a P-NH group, N3P3Cl4[O(CH2)(3)NH], (1a) or N3P3Cl4[CH3N(CH2)(3)NH], (1b) leads to formation of bis-cyclophosphazenes bridged with an eight-membered cyclophosphazene ring in an ansa arrangement (2a, 2b) whereas reaction of sodium hydride with mono-amino cyclophosphazene derivatives [N3P3Cl5(NHR), R = n-hexyl, 3a; i-Pr, 3b; Ph, 3c] give bis-cyclophosphazenes bridged with a four-membered cyclophosphazane ring in a spiro arrangement (4a-c). In the latter reaction P-O-P bridged compounds (5a-c) were also obtained as a result of hydrolysis reactions associated with the amount of moisture in the solvent tetrahydrofuran. In addition, it was found that reaction of a mixture of cyclotriphosphazene with either mono spiro compound, (1a) or (1b), in the presence of sodium hydride lead to formation of the first examples of asymmetrically-bridged cyclophosphazenes (6a-b).
Keywords: Phosphorus-Nitrogen Compounds; Chiral Configurations; Bicyclic Phosphazenes; Molecular-Structure; Ansa Dilemma; Crystal; Spiro; Chemistry; Hexachlorocyclotriphosphazatriene; Dimethylamine